Mild Traumatic Brain Injury in Major and Minor League Baseball Players. (May 2015) - Green, Gary A.; Pollack, Keshia M.; D'Angelo, John; Schickendantz, Mark S.; Caplinger, Roger; Weber, Kathleen; Valadka, Alex; McAllister, Thomas W.; Dick, Randall W.; Mandelbaum, Bert; Curriero, Frank C.
Background: Although mild traumatic brain injury (MTBI) is not as common in professional baseball as in collision sports, it does occur and frequently results in significant loss of time away from the sport. To date, no study has investigated MTBI among an entire cohort of professional baseball players. Purpose: To investigate MTBIs in major and minor league baseball players to determine the most common mechanisms of injury, activity at time of injury, position, level of play, and time lost, as well as ultimately inform prevention efforts. A secondary objective was to document the association between MTBI and return to play using several different measures. Study Design: Descriptive epidemiologic study. Methods: Data were captured from a newly implemented league-wide injury surveillance system that records injuries among all professional baseball players as entered by certified athletic trainers and physicians. The MTBIs were identified with respect to level of play, activity, field location, and mechanism of injury. Time loss was assessed by 3 measures of return to play, and MTBI game rates were reported as injuries per 1000 athlete-exposures. Data were combined over the 2011-2012 seasons for analysis, and results were presented separately for minor and major league players. Chi-square tests were used to test the hypothesis of equal proportions between the various categories of MTBI injury characteristics. Results: There were 41 reported MTBIs in the major leagues and 266 in the minor leagues over the 2-year period under study. The overall MTBI game rate across both major and minor league ball clubs was 0.42 per 1000 athlete-exposures. The median time lost was 9 days. Mild traumatic brain injury accounted for 1% of all injuries resulting in time lost from play. For MTBIs that occurred while fielding, catchers were significantly overrepresented. No differences were noted among the 3 measures of time lost. Conclusion: Mild traumatic brain injury is an important problem in professional baseball players, especially for catchers. This study provides a foundation for future inquiry to reduce the incidence of MTBI in those positions at greatest risk and to provide a baseline as rules and equipment evolve.